Mapping Researches of Green Sukuk: A Bibliometric Approach - Fauza, Nurlia; Suryomurti, Wiku (Jurnal Iqtisaduna, 2024)
This study highlights the current state of green sukuk research, conducted through journals filled with descriptions of digital objects. This analysis focuses on the character and writing style of keywords, authors, and journals. The data analyzed amounted to 123 studies published in Dimensions (https:// dimension.ai). Descriptive statistical methods were used, and bibliometric analysis was performed using R Biblioshiny to determine bibliometric maps. The number of articles discussing the green sukuk theme has been quite large in recent years. Many journals have published articles on green sukuk, most of which is the Journal of Islamic Accounting and Business Research which contains several authors who investigate the topic with various keywords, the most prolific author is Musari K., and the most widely used keyword is "green, sukuk and Islam". This study provides an overview of trends in topics, keywords, journals, and authors in popular articles about green sukuk. It provides information for researchers focused on this area. Overall, green sukuk holds immense potential to emerge as a key instrument in financing sustainable projects in the future. With concerted support from all stakeholders, green sukuk can serve as a catalyst for achieving inclusive and environmentally responsible sustainable development on a global scale. This theme can be expanded for the future.